2015
DOI: 10.1515/eces-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Hygienization of Surplus Activated Sludge By Dry Ice

Abstract: The presence of pathogenic microorganisms in sewage sludge is one of the crucial factors affecting their use in agriculture and in nature. An appropriate method of sludge hygienization can contribute to the reduction of the presence of pathogenic microbes in the sludge or to their complete elimination. This study presents the possibility of using dry ice in the hygienization of surplus activated sludge. The scope of survey covered microbiological as well as physiochemical analyses of the sludge. The microbiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Also, other authors observed a beneficial effect of sewage sludge pre-treatment with SCO 2 on its AD. As reported by Nowicka et al (2014) [27], the use of SCO 2 for SAS pre-treatment prior to AD enabled a 49% increase in biogas production in the most effective variant compared to the crude SAS [27]. At a SCO 2 /SAS ratio of 0.55/1, Zawieja (2019) [33] obtained 0.62 dm 3 /gVS biogas with a CH 4 concentration reaching ca.…”
Section: Stage 2 321 Ad Efficiencymentioning
confidence: 89%
See 1 more Smart Citation
“…Also, other authors observed a beneficial effect of sewage sludge pre-treatment with SCO 2 on its AD. As reported by Nowicka et al (2014) [27], the use of SCO 2 for SAS pre-treatment prior to AD enabled a 49% increase in biogas production in the most effective variant compared to the crude SAS [27]. At a SCO 2 /SAS ratio of 0.55/1, Zawieja (2019) [33] obtained 0.62 dm 3 /gVS biogas with a CH 4 concentration reaching ca.…”
Section: Stage 2 321 Ad Efficiencymentioning
confidence: 89%
“…S1 and S2 were divided into variants (V), depending on the volumetric ratio of SCO 2 /AGS: (control without SCO 2 ) V1, (1:10) V2, (1:5) V3, (1:3) V4, (1:2.5) V5, and (1:2) V6. The SCO 2 /AGS proportion used was estimated based on the results from the literature [27,28] and previous research [21,29]. Figure 1 presents an organizational scheme of the research.…”
Section: Experiments Organizationmentioning
confidence: 99%
“…dry ice mixed with excess sludge in a volume ratio from 0.15: 1, to 0.75: 1 and assumed a 12-hour modifi cation time. According to the literature data as a result of subjecting sludge to the freezing/ thawing process, there is an increase in the concentration of organic matter in the dissolved form expressed as SCOD, VFAs as well as TOC value (Chen 2014, Gao 2011, Nowicka and Machnicka 2013. This theory has been confi rmed by research conducted by Hong et al (Hong et al 1995).…”
Section: Disintegration Of Excess Sludge With Dry Icementioning
confidence: 88%
“…For destruction of WAS, the dry ice was used in the volume ratios of the WAS to dry ice − 1:1. In our previous work, we dealt with the efficiency of sludge disintegration and then anaerobic digestion supported with the use of dry ice (Nowicka et al 2014 ; Nowicka and Machnicka 2015 ).…”
Section: Methodsmentioning
confidence: 99%